Application Of Kegel Gymnastics And Audio Hypnobirthing In Midwife Care During Pregnancy To Reduce Urine Incontinence And Anxiety - Okta Emilia; Nurul Komariah (Poltekkes Kemenkes Palembang, 2023)
Physiological changes during pregnancy such as increased abdominal pressure and progesterone levels can make women more susceptible to urinary incontinence. As a result, more than half of women suffer from urinary incontinence during pregnancy and peaks in the third trimester. Urinary incontinence during pregnancy is a strong predictor of urinary incontinence postpartum and later in life. To prevent urinary incontinence during pregnancy, it is recommended to do pelvic floor muscle exercises (kegel exercises). In addition, the physical changes of pregnant women can also interfere with their physical and mental health so that their emotions are unstable. One of the ways that pregnant women can reduce their anxiety level is the relaxation method or self-hypnosis. Relaxation is a method that is considered quite effective for reducing muscle tension and anxiety. One of them is through audio hypnobirthing. This research was conducted to get a clearer picture of the application of the Kegel exercise method and self-hypnosis through audio hypnobirthing as an effort to reduce urinary incontinence and the resulting anxiety. This case study uses a descriptive observational method with a Continuity Of Care approach during pregnancy at Ny. N at PMB Zuniawati on 07 October 2022 to 22 October 2022. Mrs. N, who previously complained of anxiety about her pregnancy and fetus due to urinary incontinence, after being given midwifery care that was integrated with kegel exercises and self-hypnosis through audio hypnobirthing, was finally able to reduce her anxiety and expedite the delivery process